LOW CYCLE FATIGUE LIFE PREDICTION METHOD FOR SINGLE CRYSTAL NICKEL-BASE SUPERALLOYS AT HIGH TEMPERATURE - CHEN Hong; JIANG HongDe (Jixie qiangdu)
A low cycle fatigue life prediction method for single crystal nickel-base superalloys at high temperature is presented,and the method can consider the effect of average stress,strain ratio and crystal orientation on fatigue life.Firstly,a fatigue life prediction model is established to predict fatigue life of single crystal nickel-base superalloys in the [001]and [111]crystal orientations.The model considers the effect of mean stress and strain ratio on fatigue life.Then,to consider the effect of crystal orientation of single crystal nickel based superalloys on fatigue life,the relationships of fatigue parameters between[001].[111] and other different crystal orientations are given by an orientation function.Finally,the fatigue life prediction method of single crystal nickel based superalloys for other crystal orientations is proposed by using fatigue parameters of the[001]and [111]crystal orientations.The method is validated using low cycle fatigue test data of DD3 and PWA1840 nickelbase single crystal superalloy at high temperature,and the results show that the proposed method is acceptable.